The past as a stake - Napoli, Diana (História da Historiografia: International Journal of Theory and History of Historiography, 2024)
In this article, the author explores Michel de Certeau’s reflections to demonstrate how the past does not establish itself as a stable reference point for historiographical operation. Instead, it serves as a stake through which a society can transform death and loss into objects of knowledge, facilitating an exchange among the living. The text raises concerns about the present-centred experience of time, which decodes the past through an antiquarian paradigm, and about a horizon marked by the looming threat of climate change, where the future seems to disappear. Given this context, in which the role of historiography as the “topic of the intelligible” seems to have eroded, the author contemplates the possible ways of approaching the past, which, being able to accept loss, can still open up the horizon of the future.